PPARα Regulates Endothelial Progenitor Cell Maturation and Myeloid Lineage Differentiation Through a NADPH Oxidase‐Dependent Mechanism in Mice. (April 2015) - Vergori, Luisa; Lauret, Emilie; Gaceb, Abderahim; Beauvillain, Céline; Andriantsitohaina, Ramaroson; Martinez, M. Carmen
Abstract: Peroxisome proliferator‐activated receptor‐alpha (PPARα) is a key modulator of lipid metabolism. Here, we propose that PPARα regulates the maturation and function of bone marrow (BM) progenitor cells. Although PPARα deletion increased the number of BM‐resident cells and the differentiation of endothelial progenitor cells (EPCs) and monocytic progenitor cells, it impaired re‐endothelialization of injured carotid artery that was associated with reduced circulating EPCs. Also, PPARα deletion diminished the in vivo proangiogenic effect of PPARα agonist without affecting EPC differentiation markers. Macrophage colony‐stimulating factor treatment increased the population of monocytic progenitor cells as well as secretome of BM‐derived cells in PPARα wild‐type but not in knockout mice. In addition, PPARα‐null mice displayed reduced lymphocytes and increased monocytes and neutrophils in the blood. Furthermore, PPARα‐null mice exhibited increments in the number of total cells (as well as of phenotypically distinct subpopulations of lymph node cells) but also a significant alteration in the number of various subpopulations of splenocytes and thymocytes. Finally, PPARα negatively regulated reactive oxygen species derived by NADPH oxidase in BM‐resident progenitor cells. Taken together, our data provide evidence that PPARα is a critical regulator of recruitment, homing, and maturation of BM‐derived progenitor cells. Stem Cells 2015;33:1292–1303